1999
DOI: 10.1128/aem.65.2.444-449.1999
|View full text |Cite|
|
Sign up to set email alerts
|

A Strategy for Detection of Viruses in Groundwater by PCR

Abstract: We evaluated the use of the PCR for detection of enteric viruses in groundwater. To do this, we used an improved sample-processing technique and a large-volume amplification protocol. The objective of this study was to use advanced molecular techniques to develop a rapid and simple method which can be used by the water industry for detection of viral contamination in a variety of water samples. The strategy described here fulfills the water industry’s need for a rapid, reliable, easily performed method for ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(82 citation statements)
references
References 14 publications
2
68
0
12
Order By: Relevance
“…Therefore, in addition to wastewater overflows treated effluents will have to be taken into account as a significant source of viral pollution for wastewater used in agriculture and for surface waters used for aquaculture and fishery, recreational purposes or as a source for drinking water production. Moreover, both raw and treated sewage may contaminate groundwater through leakage (Abbaszadegan et al, 1999;Borchardt, 2003;Borchardt et al, 2004).…”
Section: Hazard Identificationmentioning
confidence: 99%
“…Therefore, in addition to wastewater overflows treated effluents will have to be taken into account as a significant source of viral pollution for wastewater used in agriculture and for surface waters used for aquaculture and fishery, recreational purposes or as a source for drinking water production. Moreover, both raw and treated sewage may contaminate groundwater through leakage (Abbaszadegan et al, 1999;Borchardt, 2003;Borchardt et al, 2004).…”
Section: Hazard Identificationmentioning
confidence: 99%
“…The water contamination by these agents was for domestic wastewater vector, which then can contaminate ground water and surfaces. Human enteric viruses can contaminate humans through the ingestion of contaminated water or other types of contact, such as recreational activities in contaminated marine waters (Abbaszadegan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The Polymerase Chain Reaction (PCR) is a well established and rapid method, which can be used to identify the presence of a specific virus based on the detection of its genetic material. It is a commonly used and valuable tool for assessing the microbial quality of water resources (Abbaszadegan et al 1999;Powell et al 2003). Virus detection by PCR may provide a more sensitive method of detection than cell culture assay because of the amplification process used, with low copy numbers of nucleic acid able to be detected.…”
Section: Introductionmentioning
confidence: 99%
“…It has traditionally been assumed that the use of PCR as a water quality monitoring tool will overestimate the level of microbial hazard. PCR should result in more virus being detected than cell culture assays as viral nucleic acid can be present when there are no infectious viruses present (Abbaszadegan et al 1999). However, recent studies have reported correlations between detection of virus genomes and infectivity under some specific conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation